Effectiveness of two psychological interventions in fostering tobacco smoking cessation among Nigerian commercial motorcyclists in Ibadan (2015)
This study was designed to examine the effects of covert sensitization and group therapy interventions in fostering tobacco smoking cessation among commercial motorcyclists in Ibadan metropolis. The study then adopted pre-test, post-test, control group experimental design with a 3X2 factorial matrix. The purposive sampling technique was used to select 61 participants from ten randomly selected motorcycle parks in three local government areas in Ibadan; Ibadan North, Ibadan North/West and Akinyele LGAs. The participants were randomly assigned to treatment and control groups using the ballot method. Participants in the two treatment groups were exposed to eight weeks covert sensitization and group therapy intervention programmes respectively. The results revealed that the two treatment programmes were both effective in fostering tobacco smoking cessation among the commercial motorcyclists, although the group therapy intervention was shown to be more effective than covert sensitization. It was then concluded that, clinical psychologists and other mental health care professionals would find these two approaches useful in helping smokers to quit smoking.